Cultural Differences in the Time Course of Configural and Featural Processing for Own-race Faces. (15th October 2020) - Wang, Hailing; Qiu, Ruiyi; Li, Wenyu; Li, Shouxin; Fu, Shimin
Highlights: Configural and featural face processing bias are modulated by the race of observers and the race of face stimuli. Configural face processing elicited a larger P1 under the attended own-race face condition for Chinese participants. Featural face processing elicited a larger P1 under the attended own-race face condition for Westerners. Featural face processing elicited a larger P2 under the attended own-race face condition for Chinese participants. Configural face processing elicited a larger P2 under the attended own-race face condition for Westerners. Abstract: Previous research suggests that East Asians pay more attention than Caucasian Westerners to configural information in faces, while the latter group pays more attention to featural information. However, it is unclear whether this cultural variation in attention produces a different time course of the processing bias for configural and featural information. This was examined using event-related potentials in a spatial attention paradigm. Chinese and Westerners were instructed to attend to the locations of two face images or houses. Although the race-related difference was absent in behavioral performance and N170 component, Chinese participants exhibited a configural processing bias on P1 component in the case of both own- and other-race faces and a featural processing bias on P2 component for own-race faces. In contrast, Westerners exhibited a featural processing bias for own-race faces and a configural processing bias for other-race faces on P1 component, whereas a configural processing bias was observed on P2 component for both own- and other-race faces. These results demonstrate that there are important differences between East Asians and Westerners in their relative preferences for configural versus featural processing of own-race faces, but not other-race faces. The relative roles of configural and featural information processing for faces are thus dependent on both who is looking (the culture or race of the observer) and what they are looking at (the race of the face): Easterners enjoy an early global/configural processing bias and a late local/featural processing bias for own-race faces, while Westerners benefit from an early local/featural processing bias and a late global/configural processing bias for own-race faces; both of the groups have an early and late global/configural processing bias for other-race faces.